MULTIMEDIA TEXTBOOK - PRACTICAL DEMONSTRATION OF THE SELECTED MODULE - ÖLVECKÝ, Miroslav; OLEKŠÁKOVÁ, Monika (Trends in education, 2010)
Create a quality educational environment conducive to teaching simple technical materials, designed as a support of the full-time education for pupils of the fourth year of primary school, isn't nowadays easy. Although there are several multimedia and electronic textbook, but a few of them can take a student, so they are used as support of any of the school curriculum. The paper presented some sample modules used for fixation and diagnosis of knowledge acquired during education on manual training for primary school education. The software HotPotatoes, which was selected for the creation of simple tests, short-answers, crossword, matching/ordering exercises, jumbled-sentence etc., is currently on version 6.3 provided free of charge.
Keywords: multimedia textbook; HotPotatoes; application; education.